The Epileptic Focus and the Epileptic System - Bolgaevich, Bolgayev Absadik; ugli, Boboyorov Sardor Uchkun; ugli, Eshpulatov Jaloliddin Bahodir (American Journal of Bioscience and Clinical Integrity, 2024)
The modern classification of epilepsy is an important aspect in understanding and treating this condition, as it helps improve diagnostic accuracy and therapy effectiveness. This literature review is dedicated to analyzing current approaches to epilepsy classification, including changes proposed in recent years. The article examines the main categories of epileptic syndromes, such as focal, generalized, and unspecified epilepsies, as well as their subtypes and characteristics. The significance of genetic, structural, and metabolic factors, which influence the pathogenesis of epilepsy and play an important role in choosing therapeutic tactics, is discussed. The review emphasizes the importance of integrating new technologies, such as genetic testing and functional neuroimaging, into the diagnostic process. Special attention is given to the revision of classification criteria proposed by the International League Against Epilepsy (ILAE) and its role in clinical practice.